MENELISIK METODOLOGI HISAB-RUKYAT DI INDONESIA - Sakirman, Sakirman (Hunafa: Jurnal Studia Islamika, 2011)
This paper deals with the significance of the methods of calculation (á¸¥isÄb) and observation (ruâyah) in determining the beginning of month in Islamic calendar, especially months of Â Ramaá¸Än, ShawwÄl and Å»Å« al-á¸¤ijjah, since these months have relationship with sacred Islamic rituals. However, Muslims should review and reexamine the basic method employed in determiningÂ  beginning of month in Islamic calendar. Classical dichotomy that has led to controversy until these days relates to á¸¥isÄb and ruâyah. Some said that ruâyah method is final and decisive while á¸¥isÄb is only supporting ruâyah. Others said that it is á¸¥isÄb that is final and decisive, while ruâyah is used to support the method of á¸¥isÄb. From this dispute, there should be a meeting point; that is, ruâyah should be supported by accurate science of á¸¥isÄb.